Biocompatible unimolecular micelles obtained via the Passerini reaction as versatile nanocarriers for potential medical applications - Oelmann, Stefan; Travanut, Alessandra; Barther, Dennis; Romero, Manuel; Howdle, Steven M.; Alexander, Cameron; Meier, Michael A.R. (American Chemical Society, 2018)
A Passerini three-component polymerization was performed for the synthesis of amphiphilic star-shaped block copolymers with hydrophobic cores and hydrophilic coronae. The degree of polymerization of the hydrophobic core was varied from 5 to 10 repeating units, and the side chain ends were conjugated by performing a Passerini-3CR with PEG-isocyanide and PEG-aldehyde (950 g/mol). The resulting amphiphilic star-shaped block copolymers contained thioether groups, which could be oxidized to sulfones in order to further tune the polarity of the polymer chains. The ability of the amphiphilic copolymers to act as unimolecular micellar encapsulants was tested with the water-insoluble dye Orange II, the water-soluble dye Para Red and the macrolide antibiotic azithromycin. The results showed that the new copolymers were able to retain drug cargo at pH levels corresponding to circulating blood and selectively release therapeutically effective doses of antibiotic as measured by bacterial cell kill. The polymers were also well-tolerated by differentiated THP-1 macrophages in the absence of encapsulated drugs.